Efficacy of immunization against hepatitis B virus infection in acute leukemia - Tuphan Kanti Dolai; Manoranjan Mahapatra; Hara Prasad Pati; Pravas Mishra; Tulika Seth; Rahul Bhargava; Shyam Rathi; Niranjan Rathod; Renu Saxena (Turkish Journal of Hematology, 2010)
OBJECTIVE: The aim of this study was to assess the antibody response to combined passive-active immunization versus active immunization against hepatitis B in 71 patients with acute leukemia with negative hepatitis B virus serology at presentation. METHODS: The first group (n=28) received a double dose of hepatitis B vaccine at 0, 1, 2 and 6 months and immunoglobin (HBIG) at 0 and 1 month concurrently with vaccine but at a different intramuscular site. The second group (n=43) received double dose of hepatitis B vaccine at 0, 1, 2, and 6 months. HBsAg and anti-HBs titers were determined one month after the 1st, 2nd, 3rd and 4th doses of vaccine. RESULTS: In the vaccine-only group, 2.56%, 8.33%, 14.28% and 34.29% of patients developed anti-HBs titer ≥10 IU/L after the 1st, 2nd, 3rd and 4th doses of vaccine, respectively. In the HBIG group, 91.30%, 91.30%, 69.56% and 73.91% of patients developed anti-HBs titer ≥10 IU/L after the 1st, 2nd, 3rd and 4th doses of vaccine, respectively. Those in the vaccine-HBIG group maintained their anti-HBs titer ≥10 IU/L from the 1st to the 4th doses. In the vaccine-only group, 34.29% of patients gained protective antibody titer after receiving the 4th dose of vaccine. Subgroup analysis of age (pediatric vs adult) and disease (acute lymphoblastic leukemia vs acute myeloid leukemia) groups showed no effect of either on the development of protective antibody titer. The incidence of HBsAg positivity one month after the 4th dose of vaccine was 8.62%. No patient became positive for anti-HCV or HIV antibody before or after chemo therapy. CONCLUSION: Combined HBIG and vaccine may protect acute leukemia patients during the intensive chemotherapy period.